2021
DOI: 10.3390/nano11010253
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Influence of Crystalline Form on Cyto-Genotoxic and Inflammatory Effects Induced by TiO2 Nanoparticles on Human Bronchial and Alveolar Cells

Abstract: Titanium dioxide nanoparticles (TiO2NPs) are increasingly used in consumer products, industrial and medical applications, raising concerns on their potential toxicity. The available in vitro and in vivo studies on these NPs show controversial results. Crystalline structure is the physicochemical characteristic that seems to influence mainly TiO2NPs toxicity, so its effect needs to be further studied. We aimed to study whether and how crystalline form influences potential cyto-genotoxic and inflammatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Research has provided contradictory results regarding TiO 2 NPs’ genotoxicity [ 7 , 80 ]. Several studies found TiO 2 NPs to have no genotoxic effect [ 7 , 57 , 80 , 81 ].…”
Section: Toxicity Of Tio 2 Npsmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has provided contradictory results regarding TiO 2 NPs’ genotoxicity [ 7 , 80 ]. Several studies found TiO 2 NPs to have no genotoxic effect [ 7 , 57 , 80 , 81 ].…”
Section: Toxicity Of Tio 2 Npsmentioning
confidence: 99%
“…Research has provided contradictory results regarding TiO 2 NPs’ genotoxicity [ 7 , 80 ]. Several studies found TiO 2 NPs to have no genotoxic effect [ 7 , 57 , 80 , 81 ]. Brandão et al examined TiO 2 NP-induced genotoxicity in human lung, liver, glial, and neuron cells [ 82 ].…”
Section: Toxicity Of Tio 2 Npsmentioning
confidence: 99%
See 3 more Smart Citations